New strategies in the treatment of aggressive, acutely psychotic patients : proceedings of a symposium, October 14, 1989 - Wistedt, Börje (Excerpta Medica, 1990)
Papers delivered at a symposium held on 14. 10. 1989 which discussed the treatment of aggressive, acutely psychotic patiens.
Keywords: Aggression; adherence pacienta; Clopenthixol; akutní nemoc; Acute Disease; agrese; psychiatrie; klopenthixol; psychotické poruchy; vztahy mezi zdravotnickým pracovníkem a pacientem; Professional-Patient Relations; Psychotic Disorders; Patient Compliance